2021
DOI: 10.3390/life11020177
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Insight into the Symbiotic Relationship of Pinus massoniana Lamb and Suillus luteus towards Developing Al-Stress Resistance

Abstract: Global warming significantly impacts forest range areas by increasing soil acidification or aluminum toxicity. Aluminum (Al) toxicity retards plant growth by inhibiting the root development process, hindering water uptake, and limiting the bioavailability of other essential micronutrients. Pinus massoniana (masson pine), globally recognized as a reforestation plant, is resistant to stress conditions including biotic and abiotic stresses. This resistance is linked to the symbiotic relationship with diverse ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 126 publications
1
4
0
Order By: Relevance
“…Similarly, metal tolerant S. luteus can prevent the accumulation of Zn in P. sylvestris roots (Zhang et al 2021) and improve pine growth under Cd stress, with Cd-tolerant isolates signi cantly improving pine nutrient uptake and reducing Cd needle content in high Cd concentrations (Krznaric et al 2009). Similar trends have been found in S. luteus from Asia, that reduces the toxic effects of high soil aluminum concentrations for pine partners (Liu et al 2021). These effects make metal tolerant Suillus isolates good candidates for assisting in recovering degraded sites, for example by priming seedlings for transplantation into metal contaminated soils (Branco et al 2022).…”
Section: Introductionsupporting
confidence: 78%
“…Similarly, metal tolerant S. luteus can prevent the accumulation of Zn in P. sylvestris roots (Zhang et al 2021) and improve pine growth under Cd stress, with Cd-tolerant isolates signi cantly improving pine nutrient uptake and reducing Cd needle content in high Cd concentrations (Krznaric et al 2009). Similar trends have been found in S. luteus from Asia, that reduces the toxic effects of high soil aluminum concentrations for pine partners (Liu et al 2021). These effects make metal tolerant Suillus isolates good candidates for assisting in recovering degraded sites, for example by priming seedlings for transplantation into metal contaminated soils (Branco et al 2022).…”
Section: Introductionsupporting
confidence: 78%
“…Previous studies have shown that most of the ectomycorrhizal symbioses species of C. mollissima belong to Basidiomycota [ 25 ], which includes G. viscidus and S. luteus . S. luteus has a wide distribution and has been studied in many Pinaceae plants [ 26 , 27 , 28 ]; less research has been conducted on G. viscidus . However, neither of these two types of ectomycorrhizal fungi have been thoroughly studied in Quercus .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Adriaensen et al (2005) demonstrated that inoculation with Cu-tolerant isolates of S. luteus significantly improved plant phosphorus and nitrogen uptake in Cu-contaminated soil, while Cu-sensitive isolates reduced nutrient uptake and transfer. Suillus colonization can also facilitate metal tolerance indirectly, for example, Liu et al (2020Liu et al ( , 2021) demonstrated that S. luteus activates multiple plant stress pathways, enhancing plant fitness during metal exposure. Similarly, metal exclusion mechanisms in tolerant Suillus isolates have been shown to reduce metal transfer to the host (Krupa & Kozdr oj, 2004;Zhang et al, 2021).…”
Section: Metal Tolerancementioning
confidence: 99%
“…Suillus colonization can also facilitate metal tolerance indirectly, for example, Liu et al . (2020, 2021) demonstrated that S. luteus activates multiple plant stress pathways, enhancing plant fitness during metal exposure. Similarly, metal exclusion mechanisms in tolerant Suillus isolates have been shown to reduce metal transfer to the host (Krupa & Kozdrój, 2004; Zhang et al ., 2021).…”
Section: Environmental (Abiotic) Adaptationmentioning
confidence: 99%